2019
DOI: 10.1088/1757-899x/585/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Magnesium-aluminium Spinel for Catalytic Hydrolysis of Carbonyl Sulphur at the Middle Temperature

Abstract: The influences of the physical and chemical properties for the catalyst materials on the hydrolysis catalytic activity of carbonyl sulphur (COS) and the anti-oxygen property will be crucial to removing COS from gas at moderate temperature. The magnesium-aluminium spinel for catalytic hydrolysis of COS was synthesized by the dry mixing of pseudo boehmite with MgO. The performances of the prepared catalyst were characterized by XRD, nitrogen isothermal adsorption (BET), CO2-TPD, and the COS hydrolysis activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Shangguan et al studied the performances of a synthesized magnesium−aluminum spinel in the range 150−250 °C and compared the performances with a bare alumina. 61 They observed that, in general, the MgAl 2 O 4 catalyst resulted in better performances in any experimental condition, changing the temperature and the space velocity in the range of 2000− 12 000 h −1 . The greatest difference between the undoped alumina and the magnesium−aluminum spinel was observed in the stability, which was evaluated at 250 °C and 9000 h −1 for almost 30 h. The MgAl 2 O 4 catalyst showed a reduction in conversion from 99% to 97%, while γ-Al 2 O 3 was 100% active at the beginning of the test, but the COS conversion dropped to 87% at the end of the experiment.…”
Section: High-temperature Cos Hydrolysismentioning
confidence: 97%
See 1 more Smart Citation
“…Shangguan et al studied the performances of a synthesized magnesium−aluminum spinel in the range 150−250 °C and compared the performances with a bare alumina. 61 They observed that, in general, the MgAl 2 O 4 catalyst resulted in better performances in any experimental condition, changing the temperature and the space velocity in the range of 2000− 12 000 h −1 . The greatest difference between the undoped alumina and the magnesium−aluminum spinel was observed in the stability, which was evaluated at 250 °C and 9000 h −1 for almost 30 h. The MgAl 2 O 4 catalyst showed a reduction in conversion from 99% to 97%, while γ-Al 2 O 3 was 100% active at the beginning of the test, but the COS conversion dropped to 87% at the end of the experiment.…”
Section: High-temperature Cos Hydrolysismentioning
confidence: 97%
“…Shangguan et al studied the performances of a synthesized magnesium–aluminum spinel in the range 150–250 °C and compared the performances with a bare alumina . They observed that, in general, the MgAl 2 O 4 catalyst resulted in better performances in any experimental condition, changing the temperature and the space velocity in the range of 2000–12 000 h –1 .…”
Section: High-temperature Cos Hydrolysismentioning
confidence: 99%
“…The scrubbed syngas needs to be reheated to ~250 °C in view of the efficiency of alumina-based catalysts used in COS hydrolysis [ 53 , 54 ]. The conversion of COS to H 2 S is an exothermic reaction, technically, but the passing of the syngas through COS hydrolysis can be regarded as an isothermal process in heat calculation due to the low concentration of COS.…”
Section: System Descriptionmentioning
confidence: 99%